An IT outsourcing dilemma at Sick Kids Hospital. Issue 1 (May 2018) - Babin, Ron; Khan, Mohamed; Stewart, Kyle
Abstract This teaching case is based on a true situation at the Hospital for Sick Children, in Toronto Canada. The case asks students to either assume the role of the CIO or to advise the CIO in making a decision to outsource IT at Sick Kids Hospital. The case requires students to understand three important issues: First, while health care costs continue to increase, automation of information is an important opportunity to streamline patient care and reduce costs in a hospital environment. Second, IT outsourcing, relying on external service providers to deliver complex technology services, is a fundamental business strategy across all industries and has great potential in the health care industry. Third, hospitals and health care have unique requirements for IT outsourcing, particularly the critical importance of patient data security and privacy.